2012
DOI: 10.1371/journal.pone.0042840
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Microvesicles Transfer Cystinosin to Human Cystinotic Cells and Reduce Cystine Accumulation In Vitro

Abstract: Cystinosis is a rare disease caused by homozygous mutations of the CTNS gene, encoding a cystine efflux channel in the lysosomal membrane. In Ctns knockout mice, the pathologic intralysosomal accumulation of cystine that drives progressive organ damage can be reversed by infusion of wildtype bone marrow-derived stem cells, but the mechanism involved is unclear since the exogeneous stem cells are rarely integrated into renal tubules. Here we show that human mesenchymal stem cells, from amniotic fluid or bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 34 publications
(49 reference statements)
0
66
0
Order By: Relevance
“…Other groups have reported that microvesicles/exosomes shed by CTNS-expressing cells could lead to significant cystine decrease in cystinotic cells in vitro. 45,46 This mechanism also has been described in co-culture assays of mucopolysaccharidosis VII fibroblasts with umbilical MSCs and as the mechanism responsible for the rescue of the corneal defects in mice after direct corneal transplantation of the MSCs. 47 However, we previously demonstrated using coculture assays of wild-type MSCs or macrophages with Ctns-deficient fibroblasts that, while microvesicle transfer could lead to a substantial decrease of cystine in the fibroblasts (approximately 19% clearance), TNT-mediated lysosomal transfer was a more efficient route (approximately 75% clearance).…”
Section: Discussionmentioning
confidence: 83%
“…Other groups have reported that microvesicles/exosomes shed by CTNS-expressing cells could lead to significant cystine decrease in cystinotic cells in vitro. 45,46 This mechanism also has been described in co-culture assays of mucopolysaccharidosis VII fibroblasts with umbilical MSCs and as the mechanism responsible for the rescue of the corneal defects in mice after direct corneal transplantation of the MSCs. 47 However, we previously demonstrated using coculture assays of wild-type MSCs or macrophages with Ctns-deficient fibroblasts that, while microvesicle transfer could lead to a substantial decrease of cystine in the fibroblasts (approximately 19% clearance), TNT-mediated lysosomal transfer was a more efficient route (approximately 75% clearance).…”
Section: Discussionmentioning
confidence: 83%
“…We used a mesenchymal stem cell (MSC) cell line derived from human amniotic fluid to model the effects of WT1 on EZH2-mediated silencing of CTNNB1. amMSC express the transcription factor, OSR1, a marker of the intermediate mesoderm that gives rise to the kidneys (14,15). We saw that repression of EZH2 by WT1B or siRNA led to a dramatic increase in both the expression of CTNNB1 and the activity of a ␤-catenin pathway reporter (TOPFlash) in response to WNT9b.…”
Section: Discussionmentioning
confidence: 97%
“…Cells growing in monolayer attached to plastic culture vessels after 6 -8 passages in the presence of DMEM culture medium with 15% fetal bovine serum and 1% penicillin/streptomycin were further characterized (14) and used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations